Analysis of Consumer Satisfaction Level in Taman Wisata Alam (TWA) Angke Kapuk North Jakarta - Arina Try Silvia; Harsuko Riniwati (Faculty of Fisheries and Marine Science, Brawijaya University, 2018)
One of the potential natural beauty which belong to Indonesia country is mangrove ecotourism. Located in Administration City of North Jakarta, its location in Kamal Muara village, a lush mangrove ecosystem with an area 99.82 ha. The purposes of this study are identifying the characteristics of visitors, examining the stages of the process in making decision of the visitors, analysing the responses of visitors toward the attributes, and analysing the satisfaction level of visitors toward the attributes were offered by Manager. The research method was quantitative by taking samples incidentally. The conclusions of this research are the characteristics of visitors based on gender, age, education, occupation, marital status, income per month, and domicile of the visitor; the process in making trip decision through the 5 stages; from the results of the IPA (Importance Performance Analysis) indicates the attributes that have good performance and are able to provide a satisfaction are the attributes in quadrants II and attributes that are judged as vital but the execution or performance of the attributes are still low for the consumers (lies in quadrant I), visitors in Taman Wisata Alam Angke Kapuk overall showed that the visitors satisfaction index toward the attributes were analyzed in the mount of 68.08%.